THE IMPLEMENTATION OF THE RIGHT OF INVESTIGATION OF THE HOUSE OF REPRESENTATIVES TO THE STATE INSTITUTIONS - Habibullah, Rizki (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2017)
The Right of Investigation based on article 77 (3) Law Number 7 of 2014 is the right of the House of Representatives in exercising to control the government policies. In the development the Right of Investigation is often used for the interests of the political parties. This research aim to evaluate the implementation of the Right of Investigation of the House of Representatives to the State Institutions particularly in case of the Corruption Eradication Commission and the Bank of Indonesia. This research by using constitutional and legislation approach. The results of this research found that the House of Representatives has reached the end of the process in making the Right of Investigation to the Bank of Indonesia, and the Corruption Eradication Commission that is the suggestion However there is no further implementation from the Government, the Bank of Indonesia, and the Corruption Eradication Commission. The House of Representatives has to make the Right of Investigation wisely. In the making of the Right of Investigation not merely in the basis of political interest.